Act Making Mechanisms Sale And Purchase Agreement (SPA) Public By Authentic As Evidence In The Process Of Transition Of Land - Gigih Bella Wicaksono Kenedy; Lathifah Hanim (Jurnal Akta, 2020)
SPA is a preliminary agreement on the sale and purchase agreement whose existence is recognized by Law No 1 of 2011 on Housing and Settlement (as lex), an agreement of this kind can be allocated to the object of the agreement in the form of fixed objects. The journal aims to determine: 1) Mechanism Creation Act Sale and Purchase Agreement (SPA) by the Public in the process of transfer of rights on the ground. 2) As a result of the Law of Sale and Purchase Agreement (SPA) as an Agreement.The method of this journal Sociological Juridical approach. Data were collected from literature research and field research. Data collection tool is the study of literature and interviews. Data was analyzed using qualitative approach by using inductive-deductive logic thinking.The results showed that: 1) Making mechanism Sale and Purchase Agreement (SPA) by the Public in the transition process of land rights by submitting the data themselves form: ID, KK, Certificate etc. From the data obtained all the documents submitted Copied accordance with the original, which will be attached to the Minutes of Deed Sale and Purchase Agreement (SPA) 2) The legal consequences of the Sale and Purchase Agreement (SPA) as a preliminary agreement (voor overeenkomst) is binding on the party who made it, where the parties both sellers and prospective buyers agreed to purchase land and buildings.Keywords: Transition on Land; Sale; SPA.